Humoral and Cellular Immune Response after Three Doses of Sinopharm [Vero Cell]-Inactivated COVID-19 Vaccine in Combination with SARS-CoV-2 Infection Leads to Hybrid Immunity - Marija Vukčević; Katarina Šerović; Mateja Despot; Aleksandra Nikolić-Kokić; Aleksandra Vujović; Milan Nikolić; Duško Blagojević; Tanja Jovanović; Dragana Despot (MDPI AG, 2024)
Background: Several vaccines against COVID-19 have been developed and licensed to enhance the immune response against SARS-CoV-2. Similarly, previous infection with SARS-CoV-2 has been shown to provide significant protection against severe infection and hospitalization. Methods: We investigated the effect of three doses of the Sinopharm vaccine and SARS-CoV-2 infection on the specific immune response in 103 volunteers, measuring neutralizing antibodies, anti-S1 IgG, anti-RBD IgM, anti-N IgM, anti-N IgG antibodies, and INF γ. Results: Our results showed that the presence of cardiovascular diseases increased the level of anti-N-IgG antibodies, while endocrinological diseases decreased the level of neutralizing antibodies and anti-N IgG antibodies, suggesting that these diseases alter the effect of vaccine-induced immunity. In addition, there was a significant decrease in anti-S1 IgG levels at 6 months and in anti-N IgG levels 18 months post-infection, while neutralizing antibodies and INF γ levels were constant at 3, 6, and 18 months post-infection. Conclusions: Our results confirm the emergence of hybrid immunity, which is the strongest and most durable compared to natural immunity or vaccine-induced immunity. Significant positive correlations were found between humoral and cellular immunity markers: neutralizing antibodies, anti-S1 IgG and anti-N IgG antibodies, and INF γ, indicating a unique coordinated response specific to COVID-19.